Income and democracy: Evidence from system GMM estimates - Benedikt Heid; Julian Langer; Mario Larch (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2011)
Does higher income cause democracy? Accounting for the dynamic nature and highpersistence of income and democracy, we find a statistically significant positive relationbetween income and democracy for a postwar period sample of up to 150 countries. Ourresults are robust across different model specifications and instrument sets.
Keywords: O10; C33; D72; E21; 330; Income; democracy; dynamic panel estimators; Sozialprodukt; Demokratie; Demokratisierung; Schätzung; Welt